Measurement of exclusive pion pair production in proton-proton collisions at √s = 7 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (The European physical journal. C, Particles and fields, 2023)
The exclusive production of pion pairs in the process pp → ppπ+π− has been measured at √s = 7 TeV with the ATLAS detector at the LHC, using 80 μb−1 of low-luminosity data. The pion pairs were detected in the ATLAS central detector while outgoing protons were measured in the forward ATLAS ALFA detector system. This represents the first use of proton tagging to measure an exclusive hadronic final state at the LHC. A cross-section measurement is performed in two kinematic regions defined by the proton momenta, the pion rapidities and transverse momenta, and the pion–pion invariant mass. Cross-section values of 4.8 ± 1.0 (stat) +0.3 −0.2 (syst) μb and 9 ± 6 (stat) +2 −2 (syst) μb are obtained in the two regions; they are compared with theoretical models and provide a demonstration of the feasibility of measurements of this type.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, M. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und viele weitere]
Gesehen am 12.02.2024